2013
DOI: 10.1016/j.asjsur.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Infrahepatic inferior vena cava clamping in hepatectomy for tumors involving hepatocaval confluence

Abstract: Infrahepatic IVC clamping is generally effective and safe in controlling bleeding during hepatectomy for tumors involving hepatocaval confluence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In addition, infrahepatic IVC clamping may considerably reduce the adverse effects of reduction of CVP by anesthesiological interventions and the risk of intraoperative bleeding primarily from the hepatic veins [ 27 , 28 ]. In this study, using IVC clamping to control blood loss, we were in a position to precisely identify the major vascular architecture around the hemangioma and selectively clip or ligate it, thus limiting blood loss during liver transection [ 14 ]. With fewer blood vessels traversing the capsule, the tumor can be enucleated without much blood loss by cutting open this layer between the capsule of the hemangioma and the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, infrahepatic IVC clamping may considerably reduce the adverse effects of reduction of CVP by anesthesiological interventions and the risk of intraoperative bleeding primarily from the hepatic veins [ 27 , 28 ]. In this study, using IVC clamping to control blood loss, we were in a position to precisely identify the major vascular architecture around the hemangioma and selectively clip or ligate it, thus limiting blood loss during liver transection [ 14 ]. With fewer blood vessels traversing the capsule, the tumor can be enucleated without much blood loss by cutting open this layer between the capsule of the hemangioma and the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The PM time ranged from 10 to 20 minutes with 5 min break, across studies. In the five studies reporting average PM duration, it ranged from 12.6–58.3 minutes in the IIVCC+PM group and 13.5–65.6 minutes in the PM alone group [ 11 13 , 18 , 20 ]. Only four studies reported the average IIVCC duration with it ranging from 5.5–66.5 minutes [ 12 , 13 , 18 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rahbari et al have shown that IIVCC may be more effective, in comparison to anaesthesiological interventions alone, in reducing intraoperative bleeding while minimizing the risk of hemodynamic instability [ 6 ]. Several studies have also assessed the feasibility of IIVCC combined with PM in reducing parenchymal bleeding during hepatic transection [ 10 13 ]. Conversely, some studies have also emphasized that IIVCC may also result in significant intraoperative hypotension and increase the risk of pulmonary embolism [ 6 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are 601 cases in the treatment group and 651 cases in the control group. Six of them [ 13 , 14 , 16 , 18 , 20 , 23 ] compared IVCC with control, five of them [ 15 , 17 , 19 , 24 , 25 ] compared IAC with control, and two of them [ 21 , 22 ] compared IVCC with IAC. Figure 1 shows the flow chart from literature search result to final trial inclusion.…”
Section: Resultsmentioning
confidence: 99%